TRANSNATIONAL AND POST HUMANISTIC PERSPECTIVES ON HUMAN-MACHINE COMMUNICATION - Foster, Jamie; Sawyer, Kristina; O’Connell, Carrie; Van De Wiele, Chad; Garcia, Melina (AoIR Selected Papers of Internet Research, 2018)
The proliferation of artificially intelligent robots and virtual agents raise practical, technological, and ethical considerations in the emerging area of human-machine communication (HMC) research. The topics in this panel span agriculture and environmentalism, gender and sexuality, collective identity and culture, memory and data migration, and relational development with social robots. The panel discusses ways in which technology serves as solutions to and causes of new transnational challenges for networked publics, as well as ways technology is supplanting what has historically been referred to as the “natural.” The goal of this panel is to demonstrate the diverse applications of robotics, as well as foster an open-mindset for reconceptualizing humanity in a post-human world. Specific panel presentations discuss: - Honeybee colony collapse in agriculture and artificial pollinators known as Robobees. - Industry recommendations for the development of ethical and successful caretaking robots for aging populations based on interpersonal communication scholarship. - Asymmetrical relationships and ethical implications of elevating sexbots to human status from the theoretical perspective of Rousseau’s natural self. - Digital interlocutors as scripted-selves that co-produce and standardize cultural norms. - Transference of human memory to cloud-based memory through voice commands as the foundation for algorithmic future-thinking. These research topics identify the importance and relevance of scholarship in the area of HMC and advocate for their inclusion in the conceptualization, prototyping, and creation of robotic and AI technologies. This panel offers an opportunity to engage in a necessary, provocative, and timely discussion about HMC and the role of critical scholarship in shaping technologies of the future.